CONTROL OF HEAT- AND MASS TRANSFER PROCESS IN TWO-PHASE ZONE - N. P. Voronova (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The purpose of the proposed investigation is a mathematical formulation and solution of the problem concerning selection of operating parameters of heat- and mass transfer processes while using numerical methods. The solution of the problem makes it possible to calculate changes in function describing state of the controlled media in order to obtain the desired distribution within minimum time. Results of the given paper are applicable for description of drying, blowing-up and other processes